The Influence of Green Marketing Strategy on Customer Loyalty with Mediation Role of Brand Image - Nurmahdi, Adi; Nardo, Ma Theresa Bringas; Budiono, Nur Aktif (Universitas Mercu Buana, 2025)
Objectives: The cosmetic industry has experienced significant growth, intensifying competition among beauty and personal care brands. As sustainability becomes a crucial business consideration, companies are increasingly adopting green marketing strategies to enhance their brand image and foster customer loyalty. This study examines the influence of green marketing strategies—specifically eco-labeling, sustainable packaging, green advertising, and corporate social responsibility (CSR)—on customer loyalty, with brand image serving as a mediating factor.Methodology: This study employs a quantitative approach, using survey data from 120 consumers of The Body Shop Indonesia in Jabodetabek areas. Structural equation modeling (SEM) is used to analyze the relationships between green marketing strategies, brand image, and customer loyalty.Finding: The results indicate that green marketing strategies positively influence customer loyalty, both directly and indirectly through brand image. Brand trust and perceived value play a significant role in mediating this relationship. Furthermore, authentic green marketing efforts contribute to stronger customer retention, whereas skepticism toward greenwashing diminishes brand credibility and loyalty.Practical implications of the findings provide actionable insights for brands aiming to enhance their sustainability-driven marketing efforts. Companies should focus on transparency, consistency, and consumer education to strengthen brand image and maintain long-term customer loyalty. Distinguishing authentic sustainability initiatives from greenwashing is critical in fostering trust and positive brand associations. This study contributes to the literature by providing an industry-specific analysis of the mediating role of brand image in green marketing, addressing research gaps in differentiating genuine sustainability efforts from misleading practices.Conclusion: Theoretical and practical implications underscore the importance of authenticity and transparency in green marketing communications to foster long-term customer relationships for sustainable brands.